MUTATIONAL ANALYSIS OF BETA THALASSAEMIA BY MULTIPLEX ARMS-PCR IN KHYBER PAKHTUNKHWA, PAKISTAN - Jalil, Tehmina; Yousafzai, Yasar Mehmood; Rashid, Ibrahim; Ahmed, Suhaib; Ali, Asif; Fatima, Sadia; Ahmed, Jawad (Journal of Ayub Medical College Abbottabad, 2019)
Background: Beta thalassaemia is one of the commonest genetic condition in the world. More than 200 different mutations have been reported in the beta globin chain genes. Notably, regional and ethnic variations in most common mutations in beta-thalassaemia have been identified. It is therefore imperative that region- and ethnicity- specific commonest mutations be identified for cost-effective molecular diagnosis of Î²-thalassaemia mutations. The objective of this study was to determine the molecular mutations in Î²-globin chain gene in patients with thalassemia in Khyber Pakhtunkhwa (KP) using multiplex- Amplification Refractory Mutation System (ARMS) PCR. Methods: It was a cross sectional descriptive study. Blood samples from newly diagnosed Î² thalassemia patients was collected and used as source for DNA isolation. ARMS PCR was performed for detection of mutations in Î²-globin gene. SDS-PAGE was conducted for visualization of the amplicon. Results: Prominent mutations were Fr 8-9 (+G), CD 5 (-CT) and Fr 41-42 (-TTCT). Congenital marriages and lack of awareness are largest contributing factor for increasing the disease burden. Organomegaly being a serious clinical complication which contributes to morbidity was proportional to age and disease progression. Fr 8-9 (+G) & CD 5 (-CT) were the most frequent mutation prevalent among different ethnic groups residing in KP. Conclusions: Multiplex-ARMS PCR is capable of assessing for multiple mutations in a single tube. Regional- and ethnic- variations in the commonest mutations in KP are noted. Any mutational diagnostic strategy should consider costs and genetic variations in a particular setting. Keywords: Beta Thalassemia; Î²-Thalassaemia; mutation frequency; allele distribution <!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->